Hydroxychloroquine increases the exposure of methotrexate in plasma and red blood cells: a pharmacokinetic interaction study in rats in vivo - Zhang, Guijie; Wang, Rui; Chen, Geping; Liu, Simin; Jie, Hongyu; Chen, Wenying; Li, Qiang (Frontiers in Pharmacology, 2025)
IntroductionHydroxychloroquine (HCQ) has been demonstrated to be potential to enhance the therapeutic efficacy of methotrexate (MTX) for rheumatoid arthritis (RA) patients. However, the pharmacokinetics (PK) alterations and underlying mechanisms differentiating MTX-HCQ combination therapy from MTX monotherapy remain uncharted.MethodsThirty-three Sprague-Dawley rats were divided into single-dose and multiple-dose groups, with each group further randomized into an MTX monotherapy group an Hydroxychloroquine monotherapy group (HTG), and an MTX-HCQ combination therapy group Blood samples were collected at various time points before and after dosing to determine drug concentrations in plasma and red blood cells (RBC). The area under the concentration-time curve (AUC) for each compound was calculated, and pharmacokinetics models were established to analyze parameter variations across groups.ResultsIn the single-dose group, the CTG exhibited a significant increase in the RBC MTX Cmax compared to the MTG (P = 0.023), whereas the AUC of RBC MTX showed an increasing trend (P = 0.056). In the multiple-dose group, the CTG demonstrated significant increases in plasma MTX Cmax and AUC (P = 0.023, P = 0.028, respectively) as well as RBC MTX Cmax and AUC (P = 0.010, P = 0.003, respectively). The RBC MTX polyglutamates (MTXPG2 and MTXPG3) also showed an increasing trend in Cmax and AUC for the CTG. Additionally, the CTG displayed a significant reduction in clearance rate (CLe) (P = 0.001). No significant differences were observed in the Cmax or AUC of HCQ or desethylhydroxychloroquine (DHCQ) in plasma or RBC across dosing groups.ConclusionThese findings provide insights into the enhanced efficacy, faster onset, and prolonged effect of MTX-HCQ combination therapy compared to MTX monotherapy. The observed increases in MTX Cmax and AUC suggest the need for careful monitoring of MTX-related adverse effects, particularly in patients with renal insufficiency, during combination treatment with HCQ.